2008
DOI: 10.1088/0954-3899/35/12/125201
|View full text |Cite
|
Sign up to set email alerts
|

Stellar matter with a strong magnetic field within density-dependent relativistic models

Abstract: The effect of strong magnetic fields on the equation of state (EoS) for compact stars described with density dependent relativistic hadronic models is studied. A comparison with other mean-field relativistic models is done. It is shown that the largest differences between models occur for low densities and that the magnetic field affects the crust properties of star, namely its extension. PACS numbers: 26.60.-c 26.60.Kp 97.60.Jd 24.10.Jv I. INTRODUCTIONThe study of very asymmetric nuclear matter is presently a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 51 publications
(81 reference statements)
2
66
0
Order By: Relevance
“…Similar conclusions with respect to the effect of the magnetic field on the proton fraction have been drawn in Ref. [51], where it is shown that, for B = 4.4 × 10 18 G, the magnetic field affects mainly densities below 2ρ 0 and, instead of the usual proton fractions below 0.1, proton fractions above this value are expected. An increase of the proton fraction disfavors polarization, and, therefore, in β-equilibrium magnetized matter the proton total polarization will not occur as easily.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Similar conclusions with respect to the effect of the magnetic field on the proton fraction have been drawn in Ref. [51], where it is shown that, for B = 4.4 × 10 18 G, the magnetic field affects mainly densities below 2ρ 0 and, instead of the usual proton fractions below 0.1, proton fractions above this value are expected. An increase of the proton fraction disfavors polarization, and, therefore, in β-equilibrium magnetized matter the proton total polarization will not occur as easily.…”
Section: Resultssupporting
confidence: 85%
“…[43,51]. Consequently a complete description of stellar matter requires also the leptonic contribution for the description of quantities such as the total magnetization; see Ref.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, when investigating the field effects in the EoS, it is consistent to take a magnetic field that is locally constant and uniform. This is the reason why such an approximation has been systematically used in all the previous works on magnetized nuclear [1,20,25,28,29,34,35,72,79,87,115,121,124,136,140,143] and quark matter [32,33,74,104,105,120].…”
Section: Equation Of State Of the Mcfl Phasementioning
confidence: 99%